6.1k views
21 votes
Multiply:

(x+y)by (x+y)
a+b by a^2-b^2
(a+5) by (a^2-2a-3)
(a^2-ab+b^3) by (a+b)​

User Stoefln
by
5.4k points

1 Answer

6 votes

Answer:

Multiply:


(x+y)by (x+y)


: \implies(x + y)(x + y)


: \implies \: x(x + y) + y(x + y)


: \implies {x}^(2) + xy + xy + {y}^(2)


: \implies{x}^(2) + 2xy + {y}^(2)

Multiply:


a+b \: by \: a^2-b^2


: \implies( {a}^(2) + {b}^(2) ) * (a + b)


: \implies \: {a}^(2) (a + b) - {b}^(2) (a + b)


: \implies \: {a}^(3) + {a}^(2) b - {ab}^(2) - {b}^(3)

Multiply:


(a+5) by (a^2-2a-3)


: \implies{(a + 5) * ( {a}^(2) - 2a - 3) }


: \implies \: a({a}^(2) - 2a - 3) + 5( {a}^(2) - 2a - 3)


: \implies(a * {a}^(2) - a * 2a - a * 3) + (5 * {a}^(2) - 5 * 2a - 5 * 3)


: \implies{a}^(3) - {2a}^(2) - 3a + 5 {a}^(2) - 10a - 15


: \implies{ {a}^(3) + {3a}^(2) - 13a - 15}

Multiply:


(a^2-ab+b^3) by (a+b)


: \implies{(a + b) * ( {a}^(2) - ab + {b}^(3) )}


: \implies \: a( {a}^(2) - ab + {b}^(3)) + b( {a}^(2) - ab + {b}^(3) )


: \implies {a}^(3) - {a}^(2) b + a {b}^(3) + {a^2b} - {ab}^(2) + {b}^(4)


: \implies{ {a}^(3)+ab^3 - ab^2+ {b}^(4) }

Explanation:


\blue{ \frak{Seolle_(aph.rodite)}}

User Sharmili Nag
by
5.1k points